The Ranking of municipal responsibilities importance and satisfaction in the citizens perspectives (Case study: Tehran Municipality-region 6) - leyla ghasemi; farveh rahmani; tahereh bayat (تحقیقات کاربردی علوم جغرافیایی)
Humans in the course of urban development in order to conduct the affairs of the citizens have attempted to establish a municipal entity and the duties and responsibilities to municipalities are considered. municipal performance analysis can be the best way to ensure proper duties as mayor. this study aimed to evaluate the satisfaction level of citizens the function and importance of the services that municipalities offer is made. the research method is descriptive-analytical and data collection method based on the Library, and field documents (questionnaires, respectively). Spss software was used for data analysis. statistical methods used in this paper Methods of Correlation Kendall's t-test and Kruskal-Wallis test.the results indicate that the satisfaction of the citizens of the municipality varies according to their age. satisfaction of citizens less than 40 years of municipal performance is much lower than average. and satisfaction of citizens over 40 years, is mediocre. Citizens' satisfaction with the quality of service and how information is below, but the degree of satisfaction of the authorities, employers and employees, is moderate. Among development duties-technical, service and social-cultural municipalities of the perspective of citizens in the region, there are significant differences in terms of importance. In a manner that is most important tasks of municipal services.